2019
DOI: 10.1002/mc.23120
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor‐secreted VEGF induces vascular hyperpermeability in premetastatic lung via the occludin phosphorylation/ubiquitination pathway

Abstract: Primary tumor can induce the formation of premetastatic niche. The hyperpermeability of the vessels in the premetastatic niche is the first step in the development of metastasis. However, the cellular and molecular mechanisms of vascular hyperpermeability remain to be elucidated. In this study, 4T1 breast cells were injected into the breasts of mice to establish a tumor model. Our results showed that primary tumors induced hyperpermeability of the vessels in the premetastatic lung. Subsequent studies showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…Several factors secreted by CSCs are involved in PMN formation. For example, VEGF increases vasculature permeability in the PMN [ 189 ] and stimulates MMP-9 expression in premetastatic tissue, thus facilitating tumor cell invasion [ 190 ]. Moreover, VEGF enhances the recruitment of bone marrow-derived cells (BMDCs), which are critical for PMN formation [ 191 , 192 ] and facilitate tumor-promoting microenvironment through CCL9 secretion, induced by TGF-ß signaling [ 193 ].…”
Section: Secretome In Metastasismentioning
confidence: 99%
“…Several factors secreted by CSCs are involved in PMN formation. For example, VEGF increases vasculature permeability in the PMN [ 189 ] and stimulates MMP-9 expression in premetastatic tissue, thus facilitating tumor cell invasion [ 190 ]. Moreover, VEGF enhances the recruitment of bone marrow-derived cells (BMDCs), which are critical for PMN formation [ 191 , 192 ] and facilitate tumor-promoting microenvironment through CCL9 secretion, induced by TGF-ß signaling [ 193 ].…”
Section: Secretome In Metastasismentioning
confidence: 99%
“…34,35 However, VEGFD interdiction not only inhibits pathological lymphangiogenesis but also suppresses healthy blood vessels. 36,37 On the basis of our findings, the SIRT2 expression is negatively correlated with the expression of VEGFD and lymphangiogenesis in the HNC cell, suggesting that reagent for SIRT2 might be helpful to inhibit tumor lymphangiogenesis. On the other side, EPAS1 regulates On the 25th day after injection, typical IHC staining images, the expression scores of VEGFD and SIRT2, and MVD count of Cal27 cells originated tumors were observed.…”
Section: Evidence For Sirt2-epas1 Interaction and Its Role In Tumormentioning
confidence: 61%
“…With an in‐depth comprehension of the inherent mechanism of lymphangiogenesis, agent targeting vessel pathway has been proposed as one of the most promising strategies in cancer therapy, and over the past 10 years, several antitumor lymphangiogenesis agents have been approved 34,35 . However, VEGFD interdiction not only inhibits pathological lymphangiogenesis but also suppresses healthy blood vessels 36,37 . On the basis of our findings, the SIRT2 expression is negatively correlated with the expression of VEGFD and lymphangiogenesis in the HNC cell, suggesting that reagent for SIRT2 might be helpful to inhibit tumor lymphangiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Angiogenic edema plays a key role in the occurrence and development of intractable brain edema. Vascular endothelial growth factor (VEGF) can significantly increase the vascular permeability of the tumor ( 17 ). Nassehi et al ( 18 ) found that the peritumoral edema index was positively correlated with the expression of the VEGF gene and VEGF-A protein.…”
Section: Discussionmentioning
confidence: 99%